VARIETY OF STUDY METHODS IN OPHTHALMOLOGY RESIDENCY - Abdullah, Muhammad Rizqy; Komaratih, Evelyn (Folia Medica Indonesiana, 2025)
Effective study methods are critical in ophthalmology residency, which must balance cognitive learning with surgical skill development. This systematic review examined non-surgical cognitive strategies and surgical training techniques to inform curriculum design and enhance resident performance. A structured literature search was conducted in PubMed and Scopus (2016–2025) using keywords (“study method” OR “effective study” OR “learning strategy” OR “educational intervention” OR “training approach”) AND (“ophthalmology residency” OR “resident education”). After screening and applying eligibility criteria, 17 studies were included. Methods were categorized as non-surgical (n = 5) and surgical learning (n = 12). This review revealed that non-surgical strategies, including residents-as-teachers programs, journal clubs, and structured assessments, were associated with improved engagement, knowledge retention, and board exam performance. Surgical training methods, such as wet labs, mannequin simulators, remote virtual labs, enhance psychomotor skills and procedural competence. Resident-performed surgeries showed educational benefits but suggested that students require close supervision. In conclusion, effective ophthalmology residency training integrates structured cognitive technique with simulation-based surgical practice. Active learning improves academic performance, while controlled surgical simulations of these methods across programs may optimize educational outcomes.